Analisis faktor-faktor yang mempengaruhi konsumen memilih akomodasi pada situs tiket.com di wilayah kuta selatan - Oktapiani Putri, Teodora Cikita; Putra, Agus Muriawan; Sulistyawati, Agung Sri (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 1 (2021): Vol.5,No.1,2021, 2021)
The travel sector is one of the products or services that are widely accessed through the internet today which are provided for inter-regional mobilities such as tourism and work trip. Therefore, more companies are emerging startups in Indonesia that are engaged in the field of airline ticket booking and hospitality accommodation. PT. The Global Ticket Network or commonly called Tiket.com is one of the online travel agent companies that provides hotel reservation services, airplane tickets and trains online. The purpose of this research is to to find out the factors that influence consumers to make decisions to choose accommodation and the dominant factors that contribute to influencing consumers to make decisions on Tiket.com sites in the South Kuta. The method of data collection is done by questionnaire, documentation, and library study. The sampling technique uses the Cochran formula with a sample error rate (sampling error) of 10%, the sample taken is 96.04 respondents and rounded up to 100 respondents and uses confirmatory factor analysis. The results of this study explain that there are five factors that influence consumers to make a decision to choose accommodation on Tiket.com sites in the South Kuta area and named as follow: convenience and information systems (45.978%), site visual appeal (7.196%), customer service (6.117%), company image (4,530%), and purchase motivation (4,057%). The dominating factors are convenience factors and the site information system which consists of 13 variables: (1) convenience when searching for a website, (2) time spent accessing the web, (3) company domain name used, (4 ) ease when ordering, (5) complete information, (6) accurate information, (7) information presented is interesting, (8) exposure to appropriate information, (9) availability and accessibility, (10) competitive prices , (11) overall experience, (12) security of personal data, and (13) security when making payments.